Pediatric and neonatal extracorporeal life support: current state and continuing evolution - Fallon, Brian P.; Gadepalli, Samir K.; Hirschl, Ronald B. (Pediatric surgery international, 2021)
The use of extracorporeal life support (ECLS) for the pediatric and neonatal population continues to grow. At the same time, there have been dramatic improvements in the technology and safety of ECLS that have broadened the scope of its application. This article will review the evolving landscape of ECLS, including its expanding indications and shrinking contraindications. It will also describe traditional and hybrid cannulation strategies as well as changes in circuit components such as servo regulation, non-thrombogenic surfaces, and paracorporeal lung-assist devices. Finally, it will outline the modern approach to managing a patient on ECLS, including anticoagulation, sedation, rehabilitation, nutrition, and staffing.